2021
DOI: 10.3390/ijerph18031025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Related to Working Status of Dental Hygienists in Japan

Abstract: The super-aged society of Japan is experiencing an increased demand for dental hygienists, of which there is currently a shortage. This study aimed to investigate the factors related to the working status of dental hygienists in Japan. We conducted a survey by mailing a questionnaire on employment to 1444 dental hygienists and obtained 537 valid responses. We conducted a bivariate analysis using either a chi-square test or t-test as well as a multiple logistic regression analysis to determine the factors relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…This seems to be related to the difference in employment status between NGDHs and RDHs in this study; NGDHs were more likely to work full-time, whereas RDHs tended to work part-time. This fact is also consistent with the results of a previous study in Japan, which found that fewer than half of the participants aged 30 years or older wanted to work full-time [ 13 ]. This is also consistent with studies from other countries [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This seems to be related to the difference in employment status between NGDHs and RDHs in this study; NGDHs were more likely to work full-time, whereas RDHs tended to work part-time. This fact is also consistent with the results of a previous study in Japan, which found that fewer than half of the participants aged 30 years or older wanted to work full-time [ 13 ]. This is also consistent with studies from other countries [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies have reported that the work environment of Japanese dental hygienists must be improved [ 13 , 15 , 37 , 38 ]. According to the Global Gender Gap Report 2021, Japan’s overall score in 2021 on the Gender Gap Index was 120 out of 156 countries [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this study investigated the status of oral and dental health care provision at the prefectural level and secondary medical care in Japan using the NDB. In addition, since the amount of dental care provision is closely linked to the workloads of dentists [22] and other oral and dental care workers, such as dental hygienists and dental technicians [23,24], we examined the influence of human resources and prefectural economic indicators from national statistics on the provision of oral and dental care services.…”
Section: Introductionmentioning
confidence: 99%